Precision evaluation of different flotation solutions in the results of four coprological techniques in ungulates : impact on detecting anthelmintic resistance - Silva, Pedro Afonso das Neves Pereira da (2020)
Dissertação de Mestrado Integrado em Medicina Veterinária